The MicroRNA397a-LACCASE17 module regulates lignin biosynthesis in Medicago ruthenica (L.) - Zhang, Yutong; Shan, Xiaotong; Zhao, Qiao; Shi, Fengling (Frontiers in Plant Science, 2022)
Mechanical strength is essential for the upright growth habit, which is one of the most important characteristics of terrestrial plants. Lignin, a phenylpropanoid-derived polymer mainly present in secondary cell walls plays critical role in providing mechanical support. Here, we report that the prostrate-stem cultivar of the legume forage Medicago ruthenica cultivar ‘Mengnong No.1’ shows compromised mechanical strength compared with the erect-stem cultivar ‘Zhilixing’. The erect-stem cultivar, ‘Zhilixing’ has significantly higher lignin content, leading to higher mechanical strength than the prostrate-stem cultivar. The low abundance of miRNA397a in the Zhiixing cultivar causes reduced cleavage of MrLAC17 transcript, which results in enhanced expression level of MrLAC17 compared to that in the prostrate-stem cultivar Mengnong No.1. LAC17-mediated lignin polymerization is therefore increased in the ‘Zhilixing’, causing the erect stem phenotype. Our data reveal the importance of the miR397a in the lignin biosynthesis and suggest a strategy for molecular breeding targeting plant architecture in legume forage.